Cardiovascular magnetic resonance insights into anomalies of the mitral valve apparatus in Fabry cardiomyopathy and hypertrophic cardiomyopathy - Tondi, Lara; Disabato, Giandomenico; D’Andria, Paolo; Attanasio, Andrea; Guida, Gianluigi; Pieruzzi, Federico; De Angeli, Giada; Canepa, Marco; Carrafiello, Gianpaolo; Piepoli, Massimo; Spagnolo, Pietro; Lombardi, Massimo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background and aims Despite different etiopathogenesis, Fabry Disease cardiomyopathy (FDc) and sarcomeric hypertrophic cardiomyopathy (HCM) share a similar hypertrophic phenotype, including anomalies of the mitral valve apparatus (AMVA). Some of these anomalies have also been described in the pre-hypertrophic stage of both diseases. This cardiovascular magnetic resonance (CMR) study aimed to: (i) compare AMVA between FDc and HCM with a similar degree of left ventricular hypertrophy (LVH), to add new insights into differential diagnosis; (ii) assess whether AMVA represent an early and progressive alteration in FDc; (iii) propose simple and potentially reproducible measurements of AMVA. Methods This observational, retrospective study enrolled: (i) 80 Fabry patients, divided into three groups with increasing severity of cardiac phenotype (20 patients LVH-/normal T1, 20 patients LVH-/low T1 and 40 patients LVH+), and (ii) 40 patients with HCM. All patients underwent CMR. The LVH + FDc and the HCM groups were matched for age, sex, body surface area and left ventricular (LV) mass. The following AMVA were measured on cine images: papillary muscles (PMs) hypertrophy (maximal diameter (Dmax) of anterolateral (Al) and posteromedial (Pm) PM), apical displacement, anteriorization of Al PM and anterior mitral valve leaflet (AMVL) elongation. Reference values for defining AMVA were derived from a matched healthy control group (n = 40). Results Both HCM and FDc LVH + patients showed PMs hypertrophy, with a greater degree in the FDc LVH + group [Dmax Al PM 16 ± 3.4 vs. 15 ± 3.1 mm, p 0.017; Dmax Pm PM 14 ± 4.0 vs.12 mm (10.0–14.0), p 0.039] As compared to controls, both HCM and FDc LVH + patients showed PMs apical displacement (HCM 83% vs. healthy volunteers 8%, p < 0.001; FDc LVH + 65% vs. healthy volunteers 8%, p < 0.001), with a greater prevalence in HCM. Anteriorization of Al PM was only evident in HCM (15 ± 6.2 vs. healthy controls 21 ± 5.3 mm, p < 0.001). Elongation of AMVL was detected both in HCM and FDc with LVH + (HCM 29 ± 4.0 vs. healthy volunteers 24 ± 2.9 mm, p < 0.001; FDc LVH + 27 ± 4.0 vs. healthy volunteers 24 ± 2.9 mm, p < 0.001) without significant differences between the two phenocopies. The prevalence of myocardial crypts was higher among HCM patients than in FDc LVH + patients (75% vs. 48%, p 0.012). Conclusions we report greater PMs hypertrophy in FDc and a higher prevalence of PMs positional alterations (anterior and apical displacement) and myocardial crypts in HCM. All these AMVA became more pronounced with the progression of the FDc phenotype. We suggest the systematic inclusion of the analysis of AMVA by simple linear measurements on cine images in the CMR assessment of hypertrophic cardiomyopathies, to help in the differential diagnosis between HCM and FDc and to facilitate early detection of cardiac involvement in FDc.